PENGARUH SELF EFFICACY DAN KEPUASAN KERJA TERHADAP EMPLOYEE ENGAGEMENT (KETERIKATAN KERJA) PADA GURU SMK NEGERI DI ACEH TIMUR - Muliana Muliana; Aulia Rahmi (Universitas Serambi Mekkah, 2019)
The objective of the research is find out the effect of self efficacy and job satisfaction on the teacher’s employee engagement. The research was conducted at Vocational High School in Aceh Timur. The research was using a survey method with path analysis applied in the hypothesis and 98 sample selected by simple random sampling. The research techniques is analysis with quantitative research approaches by using causal analysis. The finding of the research are: 1) there is a positive direct effect of self efficacy on employee engagement; 2) there is a positive direct effect of job satisfaction on employee engagement; 3) there is a positive direct effect of self efficacy on job satisfaction.